The Effect of Endorphin Massage on Anxiety Levels in Preoperative Caesarean Section Patients with Spinal Anesthesia at RSI Purwokerto - Ananda, Reva; Annisa, Rully (Riviera Publishing, 2025)
The level of anxiety in preoperative caesarean section patients who receive spinal anesthesia can affect physiological and psychological responses that affect surgical outcomes. Endorphin massage therapy is a relaxation technique that aims to increase endorphin production and reduce anxiety. The purpose of this study was to determine the effect of endorphin massage therapy on the anxiety level of patients before cesarean section with spinal anesthesia at RSI Purwokerto. This study used a quasi-experimental design with a pre-test and post-test approach without a control group. The sample consisted of 30 preoperative caesarean section patients selected using purposive sampling technique. Anxiety level was measured using HARS (Hamilton Anxiety Rating Scale) questionnaire before and after endorphin massage therapy. Data analysis was performed using paired statistical tests. The results showed a decrease in the patient's anxiety level before the massage intervention of 23.23 and after the intervention of 11.90, these results indicate the average difference in anxiety scores in preoperative caesarean section mothers is 11.23. Wilcoxon statistical test showed the result (p<0.05). With the conclusion that endorphin massage therapy effectively reduces anxiety levels in patients undergoing cesarean section with spinal anesthesia. This intervention can be used as a non-pharmacological method to reduce patient anxiety before surgery.